Who Should Receive Low-Dose Aspirin for Pre-eclampsia Prevention? Sorting through the Meta-Analyses - Hackney, David N.; March, Melissa I. (Current Women's Health Reviews, 2015)
Low dose aspirin has been shown to reduce the risk for preeclampsia in certain populations. The aim of this review was to provide an overview of the findings of the larger randomized trials, meta-analyses and individual patient-data meta-analysis studying this topic. It is difficult to draw exact conclusions for patient care given heterogeneity in inclusion criteria and subgroups of both the individual trials and meta-analyses. The authors’ practice is to recommend low dose aspirin to women, starting between 12 and 20 weeks gestational age, who have previously had severe and/or preterm preeclampsia in a prior pregnancy. Individual institutions are recommended to establish guidelines in order to standardize patient care, even in the context of uncertainty.
Keywords: Low dose aspirin